2018
DOI: 10.1017/pao.2018.4
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, intensity and spatial co-distribution of schistosomiasis and soil transmitted helminths infections in Ogun state, Nigeria

Abstract: A cross-sectional survey was carried out in primary schools to determine prevalence, intensity and spatial co-distribution of Schistosomiasis and soil transmitted helminths (STH) infections in Ogun State, Nigeria. A total of 2148 pupils from 42 schools were examined forSchistosomaand STH infections from urine and fresh fecal samples respectively. Ethyl ether concentration method prepared in sodium acetate – acetic acid – formalin ether was used to concentrate parasites’ ova before microscopic examination. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

15
13
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 33 publications
15
13
5
Order By: Relevance
“…The preponderance nature of Ascaris lumbricoides infections in this study corroborates with findings from recent epidemiological surveys [12,16]. Ascaris lumbricoides infections were observed in 19 of the 20 LGAs studied, with increased prevalence in the western part of the state.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The preponderance nature of Ascaris lumbricoides infections in this study corroborates with findings from recent epidemiological surveys [12,16]. Ascaris lumbricoides infections were observed in 19 of the 20 LGAs studied, with increased prevalence in the western part of the state.…”
Section: Discussionsupporting
confidence: 92%
“…In Nigeria, research findings on the geospatial distribution of Ascaris, Trichuris and Hookworm infections are scarce, but emerging [11,12,13]. This study therefore adds to the wealth of existing data on spatial distribution of these infections in Ogun State, Nigeria.…”
Section: Discussionmentioning
confidence: 91%
“…Hookworms were the most prevalent and the most widespread STH parasite in Kogi East. A similar observation was reported in Ogun State, Nigeria [31,38]. The authors attributed this to the location of Nigeria in the equatorial zone with favorable environment for the development of the larvae of hookworms.…”
Section: Discussionsupporting
confidence: 78%
“…The overall prevalence of A. lumbricoides in this study was lower than what was observed in school-age pupils of rural areas of Southern China (18.5%) [34]; southern rural Lao People's Democratic Republic (PDR) (27.4%) [35]; Jimma, Ethiopia (23.6%) [25]; Zana wereda, Ethiopia (11.5%) [4]; Ogun State, Nigeria (29.3%) [31]; and Jos, Nigeria (25.7%) [32]. The possible reason for the higher prevalence in those studies compared with this study could be that the environment of where those studies were carried out may be more favorable for completion of the life cycle of the parasite such as fertile soil, and humid and wet environment.…”
Section: Discussioncontrasting
confidence: 74%
See 1 more Smart Citation